2020
DOI: 10.36435/jgf.v18i1.432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of H/V Ratio Curve to Estimate Seismic Hazard Vulnerability in Lombok Island, West Nusa Tenggara, Indonesia

Abstract: In 2018, Lombok Island was hit by a series of destructive earthquakes. According to Indonesian Meteo- rological, Climatological, and Geophysical Agency data, about 1,973 felt earthquakes (M > 3) which shaken Lombok were recorded during August 2018 with three earthquakes with the largest magnitude of 6.9 Mw, 6.8 Mw, and 6.2 Mw. National Board for Disaster Management reported about 555 deaths, 1,833 people injured, and 186,010 houses damaged as a result of Lombok earthquake on August 5th,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The result obtained from [16] study shows high values in the western region of Lombok that can be interpreted as the alluvium deposits (Fig. 5).…”
Section: Previous Geological and Geophysical Studiesmentioning
confidence: 80%
See 4 more Smart Citations
“…The result obtained from [16] study shows high values in the western region of Lombok that can be interpreted as the alluvium deposits (Fig. 5).…”
Section: Previous Geological and Geophysical Studiesmentioning
confidence: 80%
“…There are several studies that examine about 2018 Lombok Earthquake series such as [7,10,13,16], and [17]. Reference [7] from InSAR measurements revealed that earthquake sequences occurred in Lombok on 2018 was triggered from three segments in the north side of Lombok.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations